Cell-associated pullulanase from Bacteroides thetaiotaomicron: cloning, characterization, and insertional mutagenesis to determine role in pullulan utilization. - Smith, K A (1989)
We have cloned a pullulanase gene from Bacteroides thetaiotaomicron. The pullulanase expressed from this clone in Escherichia coli was cell associated and soluble and had a molecular mass of 72 kilodaltons by gel filtration. Maxicell analysis of proteins coded by the cloned insert showed that a 71.6- to 73.2-kilodalton doublet was associated with pullulanase activity. Thus, the pullulanase is probably a monomer. The cloned pullulanase produced maltotriose as an end product of pullulan digestion. In B. thetaiotaomicron the pullulanase activity was cell associated. Approximately 80% of the activity was soluble, and 16 to 18% was membrane associated. The molecular mass of the soluble pullulanase was 77 kilodaltons by gel filtration. To determine whether the cloned pullulanase gene was essential for pullulan utilization, we used directed insertional mutagenesis to inactivate the B. thetaiotaomicron pullulanase gene. The pullulanase specific activity of the mutant was approximately 45% of that of wild-type B. thetaiotaomicron. However, the pullulanase-negative insertional mutant 95-1 was still able to grow on pullulan at a rate similar to that of wild-type B. thetaiotaomicron. Thus, there must be a second pullulanase in B. thetaiotaomicron.